2021
DOI: 10.1016/j.jbc.2021.101056
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease BIN1 coding variants increase intracellular Aβ levels by interfering with BACE1 recycling

Abstract: Genetic studies have identified BIN1 as the second most important risk locus associated with late-onset Alzheimer's disease (LOAD). However, it is unclear how mutation of this locus mechanistically promotes Alzheimer’s disease (AD) pathology. Here we show the consequences of two coding variants in BIN1 (rs754834233 and rs138047593), both in terms of intracellular beta-amyloid (iAbeta) accumulation and early endosome enlargement, two interrelated early cytopathological AD phenotypes, supporting their associatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
(134 reference statements)
1
15
0
Order By: Relevance
“…Moreover, it has been also shown that BIN1 depletion impacts BACE1 trafficking, causing its endosomal accumulation and, consequently, favoring Aβ production (Ubelmann et al, 2017 ). In line with this evidence, rare coding variants including rs754834233 or rs138047593 impact on AD risk reducing BACE1 recycling and causing early endosome enlargement recapitulating the same phenotype of Bin1 knockdown (Perdigão et al, 2021 ; Vardarajan, Ghani, et al, 2015 ). Beside this, BIN1 expression correlates also with tau pathology (Calafate et al, 2016 ), indeed it directly interacts with tau and such interaction is downregulated by tau phosphorylation on Thr231 (Sottejeau et al, 2015 ).…”
Section: Genetic and Functional Implications For Endolysosomal Dysfun...mentioning
confidence: 73%
“…Moreover, it has been also shown that BIN1 depletion impacts BACE1 trafficking, causing its endosomal accumulation and, consequently, favoring Aβ production (Ubelmann et al, 2017 ). In line with this evidence, rare coding variants including rs754834233 or rs138047593 impact on AD risk reducing BACE1 recycling and causing early endosome enlargement recapitulating the same phenotype of Bin1 knockdown (Perdigão et al, 2021 ; Vardarajan, Ghani, et al, 2015 ). Beside this, BIN1 expression correlates also with tau pathology (Calafate et al, 2016 ), indeed it directly interacts with tau and such interaction is downregulated by tau phosphorylation on Thr231 (Sottejeau et al, 2015 ).…”
Section: Genetic and Functional Implications For Endolysosomal Dysfun...mentioning
confidence: 73%
“…58,59 Notably, the presence of the K358R vari- explored, but a previous report found that K358R mutation resulted in increased accumulation of Aβ42 in vitro. 4,32 While we observe an appropriate microglial response to these plaques in terms of plaque-associated microglia, we find that the astrocytic response is profoundly blunted. We observe this through impairments in plaque-associated GFAP + astrocytes in the cortex, both in terms of number and cell size.…”
Section: Discussionmentioning
confidence: 59%
“…recycling by a larger extent (70%) compared to the P318L mutation (30%). 32 To investigate the effect of the BIN1K358R variant in vivo, we introduced the variant into the mouse Bin1 gene and interbred BIN1 K358R mice with the 5xFAD mouse model of amyloidosis, to explore its impacts on both normal brain function, as well as its interaction with aggressive amyloidosis (ie, induced by the 5xFAD transgene array). The K358R variant is located in the SH3 domain of BIN1, where it binds to proline-rich domains of proteins like Tau, clathrin, and clusterin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons are highly susceptible to disruption in the endosome/lysosome system ( 67 , 68 ). Genetic variants of endosomal proteins such as BIN1 ( 69 ), SORL1 ( 70 ), CD2AP ( 71 ) have been implicated in Alzheimer’s disease. Similarly, mutations in Vps35 ( 72 ), LRRK2 ( 73 ), and RME8 ( 74 ) are associated with Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%